Rosa Parks stays seated - Harris, Duchess (Harris, Duchess. Perspectives on American progress., 2019)
"When black bus rider Rosa Parks refused to give up her seat to a white passenger in 1955, she helped ignite a civil rights struggle across the country. Examines this historic event from multiple perspectives, including those of Parks herself, civil rights leader Martin Luther King Jr., and Parks's husband, Raymond"--OCLC.